Peningkatan Hasil Belajar Matematika Melalui Strategi Pembelajaran Planted Questions pada Siswa Kelas IV SDN 1 Campang Raya - Lestari, Yulita Dwi; Partasiwi, Nurashri; Manulang, Daya Herpiona Br (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
This study aims to improve mathematics learning outcomes through the Planted Questions learning strategy for fourth grade students of SDN 1 Campang Raya. This type of research is classroom action research with two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. In each cycle, three meetings were held. The subjects of this study were the fourth grade students of SDN 1 Campang Raya in the academic year 2020/2021 totaling 25 students. The results showed that classical student learning mastery increased from 20% in the pre-cycle to 60% in the first cycle and increased again to 84% in the second cycle. With the average value of the formative test students increased from 64.00 in the pre-cycle stage, to 72.00 in the first cycle and to 83.44 in the second cycle. Then the number of students who scored above the KKM has also increased, namely at the pre-cycle stage as many as 5 students, increasing in the first cycle to 15 students and increasing again in the second cycle to 21 students.